Experimental study on the effect of strain rates on the dynamic flexural properties of rubber concrete. (10th November 2019) - Feng, Wanhui; Liu, Feng; Yang, Fei; Li, Lijuan; Jing, Lin; Chen, Baiyu; Yuan, Bing
Highlights: Sand in concrete was replaced by crumb rubber particles at volume ratios of 10%–50%. Dynamic flexural strength and increase factor and the strain-rate effect were studied. Optimal volume fraction of rubber particles under dynamic bending was obtained. Strain-rate effect of rubber concrete in dynamic flexural tests was analyzed. Abstract: Static and dynamic flexural tests were carried out with a 100-mm-diameter split Hopkinson pressure bar (SHPB) apparatus on rubber concrete for which the fine aggregate was replaced with rubber particles made from waste tires at various volume ratios (0%, 10%, 20%, 30%, 40%, and 50%). The incident and transmission bars of the SHPB apparatus were each sleeved on a modified pad for a three-point flexural test. Experimental results showed that the flexural strength and mid-span displacement of the rubber concrete had a strain-rate effect. The rubber concrete had a more sensitive strain rate than the normal concrete when the replacement ratio of rubber particles was below 30%. However, excessive rubber content (40% and 50%) decreased the sensitivity of strain rate. The strain-rate effect of the rubber concrete was due to a short test duration, which caused more aggregates to be broken, and compressive behavior during the tests. Rubber concrete with a replacement ratio of 30% demonstrated the greatest deformability and had a lower cracking speed than the normal concrete. These results demonstrated that, under a dynamic flexural load, rubber particles can reduce the brittleness of concrete without excessive mixing.